Innovating islamic education through multiple intelligences-based learning at raudhatul huffaz center - Azka Musthofa; Maryam Hanifah; Mohamad Ali; Abdul Nizar; Aris Munandar; Mu'minah; Husna Nashihin (Yayasan Azhar Amanaa Yogyakarta, 2025)
This study aims to describe in depth the implementation of innovative learning based on Multiple Intelligences (MI) in Islamic Religious Education (PAI) subjects at Rumah Belajar Raudhatul Huffaz. This research employs a descriptive qualitative method using data collection techniques such as observation, in-depth interviews, documentation studies, and literature analysis. The results show that the application of Multiple Intelligences-based learning strategies accommodates the diversity of students' potentials, interests, and learning styles. Teachers actively design and implement various learning activities, including group discussions, worship practices, creative arts, educational games, and project-based problem solving. Each activity is structured to develop students' intelligence aspects. This innovative approach has been proven to enhance students' learning motivation, active participation, and understanding of Islamic Religious Education materials. Furthermore, the implementation fosters an inclusive and collaborative learning environment, enabling students to gain self-confidence and express their potentials optimally. Thus, the implementation of Multiple Intelligences-based learning at Rumah Belajar Raudhatul Huffaz is effective in improving the quality of both the learning process and outcomes in Islamic Religious Education, while also supporting the holistic development of students' character.